Analysis of Health Worker in Handling Complaints Management at Balikpapan Baru Hospital : A Qualitative Study - Ekawati, Muftiana Finansi (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Complaint organize was very important for hospital. The complaint can use from the patient or their family. Because they grievances can be used to improve the standard of healthcwere services offered. Apart from the fact that patient complaints can be used as information to improve the quality of health services provided, good complaint handling can improve hospital branding.in the current era of social media, hospitals were creating branding in droves. Balikpapan Baru who one of private hospital in Balikpapan which its motto “Trust Patners for your Health”. Objective : Research Methods/ Implementation Methods : The method was by conducting in-depth interviews and document reviews. The sampling technique was purposive sampling. The research instruments were the researcher himself, in-depth interview guide, observation guide, note-taking tool, notebook and recording tool. Results : Conclusion/Lesson LeaObstacles related to the flow and the person who was the verifier in handling complaints as the spearhead of the complaint handling flow can be a consideration for preparing band improving the flow in the future. including in the complaint form itself, there can be no difference between one and the other.rned :